Rearing of grouper juveniles using a demand feeding system with an infrared light sensor - Mukai, Yukinori; Nan, Hai Tai; Rosli , Muhammad Khairulanwar (2013)
Demand feeding is a new feeding method that fish can feed themselves. Fish switch on the feeding device when they require food. This method has several advantages because the fish can eat when they are most motivated to feed. The system can thus minimize feed loss and reduce water pollution. In this study, brown-marbled grouper Epinephelus fuscoguttatus and orange-spotted grouper Epinephelus coioides juveniles were reared using demand feeding devices using the commercialized and own developed demand feeders. Ten juveniles of each species were kept in a 500 L round polyethylene tank respectively (nine tanks, 90 fish). The tanks had water running system with water change (90%) every morning. Throughout the experiment, fish were exposed to natural photoperiod. Water temperature was 28.0 – 31.5 °C and salinity was 27-28 ppt. During rearing experiment, the fish were fed with pellets (Otohime EP3, Marubeni Nisshin Feed Co. Ltd.). Three experimental groups, pendulum demand feeder group (PDF, FH221, Aquatic Eco-Systems, Inc.), infrared sensor demand feeder group (IRDF) and automatic feeder group (AF) were set with three replicates. The IRDF consisted of an infrared sensor (infrared light 860 nm) ending in a red pellet-like knob with food container. Both demand feeders (PDF and IRDF) were set to dispense 10-15 pellets when fish activated the trigger (pendulum rod and infrared sensor respectively) located 2 cm below the water surface. We checked the fish circadian rhythm to determine the feeding time for the automatic feeder. The automatic feeder (AF) was set to dispense 150-170 pellets at 08:00 and 17:00 h. The experiment lasted for 25 days. Fish growth rates; total length (TL), and body weight (BW) were compared. Results of brown-marbled grouper juvenile experiments showed TL growth rates of IRDF group were significantly higher than that of PDF group (P<0.05), however, BW growth rates were similar among three groups. Results of orange-spotted grouper juvenile experiments showed no significant differences in TL and BW growth rates among three groups, but TL and BW of IRDF group showed higher tendency than that of AF and PDF groups.